Dramaturgi Sosial dalam Tradisi Grebeg Suran Sedekah Laut di Kecamatan Mirit Kabupaten Kebumen - Rini Utari; Yulianeta Yulianeta; Tedi Permadi (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
The Grebeg Suran Sedekah Laut tradition, as a form of cultural expression of coastal communities, can serve as a collective medium for preserving local identity and strengthening social solidarity. This study aims to analyze the Grebeg Suran Sedekah Laut tradition through a social dramaturgy approach to reveal the dynamics of social roles, impression management, and social structures reflected in cultural practices. This study employs a descriptive qualitative approach. The theoretical framework used in this study is Goffman's social dramaturgy theory. The participants in this study include community leaders who serve as key informants, fishermen, and the general public in Mirit Sub-district, Kebumen Regency. Data collection techniques include interviews and observations at Wuni Melodi Miritpetikusan Beach, Laguna Lembupurwo Beach, and the Rowo Village river. Research data is analyzed using the Miles, Huberman, & Saldana model, starting from data reduction, analysis, verification, and conclusions. The results of the study indicate that in this tradition, the community acts as social actors who play roles on the cultural stage through ritual processes such as offering ceremonies and communal prayers. There is a division of roles between traditional leaders, fishermen, and the community within a structure that reflects social norms and collective values. Elements such as front stage, back stage, setting, and impression management are clearly present in this tradition, demonstrating that the practice of tradition is not only a spiritual ritual but also a form of social performance that reinforces the values of mutual cooperation, religiosity, and cultural identity of the community. This research enriches the interdisciplinary perspective on oral traditions and underscores the importance of cultural preservation based on local wisdom.